2018
DOI: 10.1002/cc.20305
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Pedagogical Challenges in Developmental Education Reform

Abstract: This chapter presents pedagogical challenges to reform in developmental education and observations of best practices gleaned from successful mathematics developmental education classrooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Semi‐structured interviews were conducted using protocols developed for our mixed‐methods study that utilized previous literature on developmental education (CCRC, 2014; Cox, 2018; Edgecombe et al., 2013). Interview protocols differed as faculty were asked more about teaching tools/strategies, while prompts for student success deans focused on advising strategies and collaborating with academic departments on the corequisite model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi‐structured interviews were conducted using protocols developed for our mixed‐methods study that utilized previous literature on developmental education (CCRC, 2014; Cox, 2018; Edgecombe et al., 2013). Interview protocols differed as faculty were asked more about teaching tools/strategies, while prompts for student success deans focused on advising strategies and collaborating with academic departments on the corequisite model.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, faculty as key instructional leaders are vital to the success of corequisite courses since community college students often interact and spend more time with faculty in the classroom than any other professional (ACUE & Sova, 2021). The important role faculty play is underscored by studies that have revealed promising student success outcomes when faculty use innovative teaching approaches in developmental education (Cox, 2018; Grubb & Gabriner, 2013; Logue et al., 2019; Rutschow, 2018). In developmental education research, there is also a push to implement more classroom‐level reform efforts to address faculty teaching strategies (D'Antonio, 2020; Henry & Stahl, 2017; Nabb & Murawska, 2020; Richardson, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these resources, studies of developmental education reform implementation at institutions have shown that faculty professional development is a critical area of need (Daugherty et al., 2018). Not surprisingly, a range of pedagogical questions and challenges accompany reforms, including how to maximize opportunities for learning, meet the needs of diverse students, and scaffold supports for the most academically vulnerable students (Bickerstaff & Cormier, 2015; Cox, 2018). Consider also that developmental courses are more likely to be taught by part‐time faculty who have less access to professional learning opportunities (Center for Community College Student Engagement, 2014).…”
Section: Developmental Education Reformmentioning
confidence: 99%
“…Intermediaries, state systems, and other organizations that define and promote these reforms have a role to play in emphasizing the value of instructional improvement in reform efforts. Researchers that evaluate their effectiveness can look not only at student progression metrics (i.e., course completion) but also at measures of student learning (Cox, 2018). The barriers to centering instructional improvement work are significant, but through coordinated action grounded in ongoing reform, community colleges have an opportunity to make high‐quality teaching and learning a strategic priority.…”
Section: How a Systems Approach Can Support Institutional Commitment To Instructional Improvementmentioning
confidence: 99%